ISOLASI DAN KARAKTERISASI SENYAWA DARI EKSTRAK DAUN BOTTO-BOTTO (Chromolaena odorota L.) YANG BERPOTENSI SEBAGAI ANTIKANKER - Rusdi, Muhammad; Fatmasyarif, Evi; Ananda, Citra Rezki (Jurnal Kesehatan, 2020)
This study aims to isolate and identify botto-botto compounds that have the potential to be anti-cancer. Methanol solvent assists the extraction of simplicia of botto botto leaves through maceration method. The methanol extract was partitioned with n-Hexan and ethyl acetate solvents to obtain n-Hexan and ethyl acetate fractions. Each fraction was then fractionated again by vacuum liquid chromatography to obtain isolates. The obtained isolates have characteristics using UV-Vis spectrophotometry and FT-IR spectrophotometry. The results obtained 2 compounds (Isolate HB3D3 from the n-Hexan fraction and Isolate EB6A5 from the ethyl acetate fraction). The results of the identification of isolate HB3D3 and isolate EB6A5 against the appearance of the compound group spots showed that the HB3D3 and EB6A5 isolates were terpenoid compounds. Isolate HB3D3 is a terpenoid with the characteristics of the presence of bound OH groups, aliphatic C-H, monosubstituted aromatic rings, C = O and alkenes. Isolate EB6A5 is a terpenoid with the characteristics of the presence of bound OH groups, aliphatic C-H, monosubstituted aromatic rings, C-O-C, C-O ether and alkenes.